Benign inflammatory cervical smear in a background of normal diagnostic dilatation and curettage finding - a rare presentation of endometrial carcinoma - Shalihin, Mohd Shaiful Ehsan; Harun, Zulkifli; Osman, Iskandar Firzada (Society for Advance Healthcare Research, 2018)
Endometrial carcinoma is a primary tumor of the uterus that usually presented with abnormal uterine bleeding commonly in post-menopausal woman. However, it can also manifests as abnormal cervical cytology even in a pre-menopausal age group which should be confirmed by endometrial biopsy.[1,2] There is no evidence to support mass screening for endometrial carcinoma in view of low efficacy of the test and lack of cost-effective benefit in detecting the disease.[1,2] Nevertheless, cervical screening is really useful in reducing risk of invasive cervical cancer and reduced the mortality. It is available at primary care centres and indirectly useful for endometrial carcinoma detection.[2,3] Dilatation and curettage (D&C) is an invasive and diagnostic procedure to identify specific causes for abnormal uterine bleeding with high sensitivity of up to 99% in detecting endometrial lesions.[1,2] We would like to report a case of a rare presentation of early endometrial carcinoma manifested as incidental findings of benign inflammatory cervical changes in a low suspicious patient in view of clear findings of the initial diagnostic D&C.